VILLAGE GOVERNANCE TRANSFORMATION THROUGH E-GOVERNMENT (STUDY OF SUGIHWARAS VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY) - Suwanti, Julia Eka Cesar; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the transformation of village governance through the implementation of e-Government in Sugihwaras Village, Candi District, Sidoarjo Regency. The focus of the research is directed at how the implementation of digital innovation can improve the quality of public services, transparency, accountability, and community participation in village governance. Methods: The research method used was qualitative descriptive with a case study approach. Data was collected through observation, in-depth interviews with village officials, and documentation. Data analysis was carried out thematically by referring to Dwiyanto's  theory of bureaucratic performance indicators, including productivity, service quality, responsiveness, responsibility, and accountability.   Results: The results of the study show that the implementation of digital applications such as SIPRAJA, Prodeskel, the Building Village Index (IDM), and the Data Desa Center (DDC) is able to accelerate administrative services, increase transparency in the use of Village Funds, strengthen bureaucratic accountability, and expand community participation through online complaint services. However, obstacles are still encountered in the limited number of human resources (especially elderly village devices), unequal internet access, and lack of budget support for sustainable development.  Novelty: The novelty of this research lies in the analysis of the village digital transformation roadmap which is prepared in stages, starting from strengthening infrastructure, increasing human resource capacity, integrating digital services, to participatory monitoring and evaluation. This approach shows that the success of digital transformation is not only determined by technology, but also by community involvement, regulatory support, and visionary village leadership.